KERJASAMA PERTAHANAN INDONESIA DENGAN FILIPINA DALAM MEMBERANTAS PIRACY AND ARMED ROBBERY AGAINTS SHIP PERIODE 2012-2015 - Miftha Loro Maisitha, - (2018)
This paper discusses Indonesia's Defense Cooperation with the Philippines in Combating Piracy and Armed Robbery Against Ship which is often faced with crime problems especially hostage taking and ship hijacking. Indonesia and the Philippines have conducted patrols, intelligence and joint training in the waters of sulu but the crime rate in the region is still relatively high. The approach to be seen in this paper is the formation of bilateral cooperation, in which the government needs to do a fairly binding defense cooperation. Indonesia as a country with significant territorial interests in the region must initiate follow-up of meetings that have been held between the two countries. The Sulu Sea includes a dangerous cruise line